Real practice infammation indicator in patients with wet AMD and anti-VEGF treatment - Король, Андрій Ростиславович; Трояновська, Ксенія Володимирівна; Зборовська, Олександра Володимирівна; Дорохова, Олександра Едуардівна; Горянова, Ільїна Сергіївна; Колесніченко, Вікторія Віталіївна; Кустрин, Тарас Богданович; Насінник, Ілля Олегович (My University, 2024)
Introduction: HAWK and HARRIER studies showed possible infammation after intravitreal injections mostly of brolicizumab. In routine practice we have to fnd some predictors of such infammation. Objectives: indices of laser fare photometry in anterior chamber of patients before and after inravitreal injections of afibercept and brolicizumab Aims: To study the level of intraocular infammation by laser fare photometry in patients with the wet AMD and anti-VEGF treatment in real practice. Methods: Open-label comparative prospective interventional study was conducted in The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine, Odesa, Ukraine. Inclusion criteria: only primary, untreated patients with the wet form of age-related macular degeneration, participated in the study. Exclusion criteria: any intraocular surgery including cataract or glaucoma surgery; history of any kind of intraocular infammation. Treatment: the frst group of patients underwent intravitreal administration of 2 mg (0.05 ml) of afibercept, in the second group, 6 mg (0.05 ml) of brolucizumab according to fxed schedule. The primary point of the study: the dynamics of the laser fare photometry indicator of infammation during 6 months of observation. The secondary point: the dynamics of the median BCVA and the thickness of the central retina in the 6 months of observation compared to the baseline. Results: 20 patients (23 eyes) were included in the study. The afibercept group included 12 patients (14 eyes). The brolucizumab group included 8 patients (9 eyes). The median objective indicator of infammation at baseline in the afibercept group was 6.3 ph/ms (from 2 to 17.3 ph/ms), after 6 months it was 4.5 ph/ms (from 2.7 to 6.9 ph/ms), p = 0.5. In the brolucizumab group, the median objective indicator of infammation at baseline was 6.95 ph/ms (from 4.7 to 19 ph/ms), after 6 months it was 7.1 ph/ms (from 5 ph/ms to 9.2 ph/ms), p = 0.4. During the entire observation period, there were no statistically signifcant changes in the laser fare photometry indicator in the two groups. The median infammation indicator at the beginning and at 6 months did not difer statistically signifcantly between groups p = 0.7 and p = 0.2 respectively. Conclusion: Intravitreal administration of afibercept and brolucizumab in primary patients with the wet AMD does not lead to an increase of laser fare photometry indicator in 6 months, in the fxed regimen.